Creating a 'FatherConfessor': the origins of research ethics committees in UK military medical research, 1950–1970. Part I, context and causes. Issue 4 (4th August 2019) - Schmidt, Ulf
Abstract : Part I provides the historiographical context and examines the causes which led to the creation of the first independent research ethics committee (REC) at Porton Down, Britain's biological and chemical warfare establishment, in operation since the First World War. The papers in part I and part II argue that the introduction of RECs in the UK stemmed from concerns about legal liability and research ethics among scientists responsible for human experiments, and from the desire of the UK military medical establishment to create an external organisation which would function both as an ' internal space ' for ethical debate and as an ' external body ' to share moral and legal responsibility. The paper asks: What factors were responsible for causing military scientists and government officials to contemplate the introduction of formalised structures for ethical review within the UK military? It argues that Porton may have been exempt from public scrutiny, but it was not above the law of the land. By the mid-1960s evidence of serious ill effects among staff members and service personnel involved in tests could no longer be ignored. Whereas the security of the British realm had previously trumped almost any other argument in contentious debates about chemical warfare, the role of medical ethics suddenly moved to the forefront of Porton's deliberations, so much so that tests with incapacitants were temporarily suspended in 1965. It was this crisis, examined in detail in part II, which functioned as a catalyst for the creation of the Applied Biology Committee as the responsible body, and first point of call, for authorising human experiments at Porton Down.